2016
DOI: 10.1158/0008-5472.can-15-0484
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Recurrently Deregulated Genes across Multiple Cancers Identifies New Pan-Cancer Biomarkers

Abstract: Genes that are commonly deregulated in cancer are clinically attractive as candidate pan-diagnostic markers and therapeutic targets. To globally identify such targets, we compared Cap Analysis of Gene Expression profiles from 225 different cancer cell lines and 339 corresponding primary cell samples to identify transcripts that are deregulated recurrently in a broad range of cancer types. Comparing RNA-seq data from 4,055 tumors and 563 normal tissues profiled in the The Cancer Genome Atlas and FANTOM5 dataset… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 39 publications
5
74
0
Order By: Relevance
“…Furthermore, a study conducting a pan-cancer investigation noticed that promoters containing SINE, LINE, and LTRs were upregulated in cancers (38). In our study and in concordance with previous studies, we observed that the majority of LTR and LINE elements were upregulated in EAC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, a study conducting a pan-cancer investigation noticed that promoters containing SINE, LINE, and LTRs were upregulated in cancers (38). In our study and in concordance with previous studies, we observed that the majority of LTR and LINE elements were upregulated in EAC.…”
Section: Discussionsupporting
confidence: 92%
“…In our study and in concordance with previous studies, we observed that the majority of LTR and LINE elements were upregulated in EAC. Our study also confirms the upregulation of REP522, which has previously been indicated in cancer (38). What differs from previous studies is that we observed a downregulation of SINE in EAC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The overlapping genes included TOP2A, which is upregulated across multiple cancer types (15,40), and six kinases including AURKA and AURKB that are implicated in various cancer types (41). Among 22 epi-markers, IGF2BP3 and CEP55 (associated with poor survival in LUAD as described before) showed highest correlations with the cell-cycle genes (Supplementary Fig.…”
Section: Correlations With Epigenetic Factorsmentioning
confidence: 69%
“…The thresholds of absolute fold change > 2 and FDR < 0.05 were used. We also evaluated the expression status in binary fashion: ON (expressed, count > 0), OFF (not detected, count ¼ 0), as described before (15). In short, we calculated the frequency of expression (OFF/ON analysis), and features expressed four times more frequently in NSCLC were determined as turned ON.…”
Section: Fantom5 Cage Datamentioning
confidence: 99%